Cardiovascular Risk Factors and Brain Health: Impact on Long‐Range Cortical Connections and Cognitive Performance. Issue 23 (4th December 2018) - Marebwa, Barbara K.; Adams, Robert J.; Magwood, Gayenell S.; Basilakos, Alexandra; Mueller, Martina; Rorden, Chris; Fridriksson, Julius; Bonilha, Leonardo
Abstract : Background: Cardiovascular risk factor burden in the absence of clinical or radiological "events" is associated with mild cognitive impairment. Magnetic resonance imaging techniques exploring the integrity of neuronal fiber connectivity within white matter networks supporting cognitive processing could be used to measure the impact of cardiovascular disease on brain health and be used beyond bedside neuropsychological tests to detect subclinical changes and select or stratify participants for entry into clinical trials. Methods and Results: We assessed the relationship between verbal IQ and brain network integrity and the effect of cardiovascular risk factors on network integrity by constructing whole‐brain structural connectomes from magnetic resonance imaging diffusion images (N=60) from people with various degrees of cardiovascular risk factor burden. We measured axonal integrity by calculating network density and determined the effect of fiber loss on network topology and efficiency, using graph theory. Multivariate analyses were used to evaluate the relationship between cardiovascular risk factor burden, physical activity, age, education, white matter integrity, and verbal IQ. Reduced network density, resulting from a disproportionate loss of long‐range white matter fibers, was associated with white matter network fragmentation ( r =−0.52, P <10 −4 ), lower global efficiency ( r =0.91, P <10 −20 ), and decreased verbal IQ (adjusted R 2 =0.23, P <10 −4 ). Conclusions: Cardiovascular risk factors may mediate negative effects on brain health via loss of energy‐dependent long‐range white matter fibers, which in turn leads to disruption of the topological organization of the white matter networks, lowered efficiency, and reduced cognitive function.